Reassessment of Sphenoid Dysplasia Associated with Neurofibromatosis Type 1 - Jacquemin, Claude; Bosley, Thomas M.; Liu, Don; Svedberg, Helena; Buhaliqa, Amal (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Sphenoid dysplasia associated with neurofibromatosis type 1 is classically thought to be primarily related to abnormal development of the sphenoid bone. We investigated the possibility that these changes may be progressive.METHODS: We conducted a retrospective review of sphenoid bone changes in all patients with craniofacial neurofibromatosis type 1 who had undergone CT (31 patients) and MR imaging (seven patients) at our facility. A review of repeat images of 20 patients permitted analysis of progressive sphenoid bone changes.RESULTS: Eighteen patients had abnormalities of the sphenoid wings, 13 of whom also had enlargement of the middle cranial fossa compatible with descriptions of classic sphenoid dysplasia. All the patients with sphenoid dysplasia had neurofibromas in the ipsilateral superficial temporal fossa that were often contiguous with a radiologically abnormal temporo-squamosal suture. All except one had tumor infiltration in the deep orbit, contiguous with the sphenoid wings. Four patients had radiologic evidence of progressive sphenoid bone changes over time.CONCLUSION: The origin of sphenoid bone changes may be multifactorial. A modified concept of sphenoid dysplasia is proposed that emphasizes interaction between neurofibromas and sphenoid bone during skull development.